Velikost zenice med izvajanjem ravnotežnih nalog - Leskovec, Tinka (Šport (Ljubljana), 2021)
More challenging balance tasks demand increased postural control and could present an increased load of the cognitive system. Changes in cognitive load could be mirrored in pupil size dilatation which can be measured with pupillometry. The aim of this study was to analyse whether changes in stiffness and size of support surface cause changes in pupil size diameter. Twenty healthy young adults participated in the study and performed bilateral stance on a stabile flat surface and unilateral stance on two different support surfaces (solid flat surface and soft surface). Pupil diameter and basic parameters of the centre of pressure movement (sway velocity and average frequency) were analysed. Statistically significant differences in pupil diameter and sway velocity were observed between unilateral stance on solid flat surface and unilateral stance on soft surface. The results of the study indicate when support surface changes from a solid to soft, the average pupil size increases (~ 10 %). Furthermore, performing unilateral stance on a soft surface represents a greater cognitive load than performing unilateral stance on a solid surface.
Keywords: balance; cognitive load; pupillometry; pupilometrija; ravnotežje; somatosensory inflow; somatosenzorni priliv; sport; spoznavna obremenitev; šport